2020
DOI: 10.1002/adfm.201908919
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Programmable Dip Molding of High Aspect Ratio Soft Actuator Arrays

Abstract: This work presents multiple methods of creating high aspect ratio fluidic soft actuators that can be formed individually or in large arrays via dip coating. Within this methodology, four strategies are provided to mechanically program the motion of these actuators, including the use of fiber inclusions, gravity, surface tension, and electric fields. The modular nature of this dip coating fabrication technique is inexpensive, easy to modify, and scalable. These techniques are used to demonstrate the fabrication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…Similarly, the use of GE as a nanofiller was shown by Ren et al [ 17 ], Liao et al [ 18 ], Zhang et al [ 19 ], and Wei et al [ 20 ], and improved properties were reported that are amenable to the development of next-generation polymer composite materials. The small particle size [ 21 ], high aspect ratio [ 22 ], and optimum surface area [ 23 ] of these nanofillers allow for the achievement of good mechanical and electrical properties at low filler content, as demonstrated by Khanna et al [ 24 ], Wang et al [ 25 ], Wu et al [ 26 ], and Wei et al [ 27 ]. These authors reported CNTs as a single or hybrid filler in various matrices, and improved properties were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the use of GE as a nanofiller was shown by Ren et al [ 17 ], Liao et al [ 18 ], Zhang et al [ 19 ], and Wei et al [ 20 ], and improved properties were reported that are amenable to the development of next-generation polymer composite materials. The small particle size [ 21 ], high aspect ratio [ 22 ], and optimum surface area [ 23 ] of these nanofillers allow for the achievement of good mechanical and electrical properties at low filler content, as demonstrated by Khanna et al [ 24 ], Wang et al [ 25 ], Wu et al [ 26 ], and Wei et al [ 27 ]. These authors reported CNTs as a single or hybrid filler in various matrices, and improved properties were reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth step, the downside channels were sealed. The step-by-step fabrication processes along flow charts can be found in the study [ 73 ].…”
Section: Fabrication Techniques For Artificial Ciliamentioning
confidence: 99%
“…Electric stimulation is another approach to remotely and precisely control artificial cilia. [ 75 ] For example, artificial cilia composed of dielectric elastomer has been presented, which could deform when exposed to an alternating‐current (AC) electric field. [ 76 ] The matrix material of such cilia was PDMS and electrosensitive barium titanate (BaTiO 3 ) nanoparticles were embedded inside.…”
Section: Actuating Strategies For Artificial Ciliamentioning
confidence: 99%